FARMERS AWARENESS ON RESPONSIBLE USE OF PESTICIDES IN CUCURBIT GROWING AREAS OF GUNTUR DISTRICT - A. DEVI VARAPRASAD SAI*, CH. SREENIVASA RAO, D.V. SAIRAM KUMAR, D. RAMESH; CH. TIRUMALA DEVI (The Journal of Research ANGRAU, 2021)
The study on farmer’s awareness on pesticides use and handling was conducted in cucurbit growing areas of Guntur district during the year 2020. A large number of cucurbit farmers (86.7%) were not aware about the registered and recommended pesticides on cucurbits as per the Insecticide Act, 1968, while, only 6.6% were aware about the ban of ‘monocrotophos’ on vegetables. All cucurbit farmers consulted pesticide dealers as source of recommendations, whereas, few young farmers consult Agricultural Officers in addition to the dealer. About 56.7% farmer’s measured pesticide approximately, others used measuring cup while preparing spray fluid and all the farmers used stick for mixing spray fluid. More than half of the spray men (57.0%) did not use any kind of personal protection equipment, while, 20.0% wore separate clothes with full-sleeves covering the entire hands, only 17.0% spray men wear gloves, and only 6.7% used face mask. Empty pesticide bottles are reused for household purposes by 33.3% of the farmers, and most of the farmers (86%) throw the empty / used pesticide bottles /containers in trash bins or open fields, and none of the farmers were aware of the proper disposal methods.